DIVERSITY AND THE MOST COMMON TRADED SPECIES IN THE SUDANESE MEDICINAL PLANTS - Khalid, H.; Abdalla, W. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The paper covers the most common species used in Sudanese folk medicine in the five floristic belts. In the desert belt the most common species are Ziziphus spina-christi L, Boscia senegalensis (Pers.) Lam. Cadaba farinosa Forssk, Fagonia cretica. Species of the semi-desert belt include Salvadora persica L., Maerua crassifolia Forssk., Capparis decidua Forssk., Acacia senegal (L.) Willd., Acacia nubica Benth. Ziziphus spina-christi (L.) Balanites aegyptiaca (L.) Leptadenia pyrotechnica (Forssk.) DC Senna alexandrina Mill. (Cassia senna L.) Calotropis procera (Ait.). Thorn Savanna & scrub belt flora include, Albizzia amara (Roxb.) Boiv. Sclerocarya birrea (A.Rich.) Hochst. Cadaba glandulosa Forssk, Dalbergia melanoxylon Guill. & Perr. Acacia seyal Del. Calotropis procera (Ait.) Ait. f. Acacia senegal (L.) Willd., Balanites aegyptiaca (L.) Del. Species of the deciduous Savanna are Combretum hartmannianum Schweinf., Terminalia brownii Fresen., Khaya senegalensis (Desr.) A.Juss, Albizzia amara (Roxb.) Boiv., Acacia seyal Del. and the flood region flora cover Hyphaene thebaica (L.) Mart., Acacia polyacantha Willd. The most common species in trade records (imports and exports) were reported for the last five years (Dec. 2003 – Dec. 2007).